Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd007402.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Topical NSAIDs for acute pain in adults

Abstract: Topical NSAIDs can provide good levels of pain relief, without the systemic adverse events associated with oral NSAIDs, when used to treat acute musculoskeletal conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
10

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 106 publications
(76 citation statements)
references
References 37 publications
1
65
0
10
Order By: Relevance
“…Важным преимуществом локальных НПВП является достижение высокой концентрации активного вещества в пораженной области при более низкой его концентрации в плазме крови, что дает возможность значительно умень-шить риск развития системных нежелательных явлений [76]. Наиболее удобной формой для противовоспалитель-ной локальной терапии является гель.…”
Section: д и н а м и к а п о к а з а т е л е й с у с т а в н о г о с unclassified
“…Важным преимуществом локальных НПВП является достижение высокой концентрации активного вещества в пораженной области при более низкой его концентрации в плазме крови, что дает возможность значительно умень-шить риск развития системных нежелательных явлений [76]. Наиболее удобной формой для противовоспалитель-ной локальной терапии является гель.…”
Section: д и н а м и к а п о к а з а т е л е й с у с т а в н о г о с unclassified
“…However, there is still debate on these potential advantages as there is continuous lack of significant positive results 2–4. A Cochrane review update was recently carried out to assess the effect of topical NSAIDs used for acute musculoskeletal pain in adults 5. This review aimed to strengthen conclusions on the efficacy and safety of topically applied NSAIDs in acute musculoskeletal pain in adults, adding recently published studies to the previous search.…”
Section: Contextmentioning
confidence: 99%
“…A Cochrane review in 2010 of 47 double blinded RCTs showed that topical diclofenac, ibuprofen, ketoprofen, and piroxicam are significantly more effective and as safe as topical placebo in the treatment of acute musculoskeletal pain 27. The review did not address the safety of chronic use.…”
Section: Advances In Nsaid Analgesiamentioning
confidence: 99%